Podstawowe założenia MSSF 1 - zastosowanie Międzynarodowych Standardów Sprawozdawczości Finansowej po raz pierwszy - Kogut, Joanna (Fundamental Assumptions of MSSF 1 - the Application of International Financial Reporting Standards for the First Time, 2006)
The objective of the hereby article is to discuss basic regulations included in FAIS 1 "Application of Financial Accounts International Standards for the first time" and their influence on accountancy practice. Special attention was paid to facultative and obligatory exclusions covered by the standard regarding most important issues resulting from changing into FAIS. FAIS is of significant importance due to preparations for the common application of IAS till 2005 by the European public companies with regard to the European Union strategy related to accountancy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (5); 2006; nr 1120, s. 117-128